Health risks of workers fish farming center - Minchola Gallardo, Jorge L. (2013)
In this study we evaluated the ergonomic risks in workers' health Fish Farming Center. The sample universe consisted of the 15 workers of Motil Fish Farming Center, Department of La Libertad, Peru. Samples were taken every month. The methods used to assess ergonomic ergonomic risk were: Job Strain Index (JSI), Rapid Entire Body Assessment (REBA) and Oako Working Analysis System (OWAS). The Results demonstrated by the methods of JSI and REBA that selection and maintenance activities are generating greater risks, and, according to the method OWAS, the activity that generates higher risks is that of selection, followed by selection activities of gravid females and maintenance. It was concluded that the activities that need immediate corrective measures are the selection and maintenance.